The Effect of Third Party Funds, Credit Risk, Loan to Deposit Ratio and Capital Structure on Profitability in Banking Companies Listed on the Indonesia Stock Exchange: The Effect of Third Party Funds, Credit Risk, Loan to Deposit Ratio and Capital Structure on Profitability in Banking Companies Listed on the Indonesia Stock Exchange - Revi Arfamaini (International Journal of Business and Quality Research, 2023)
A healthy or unhealthy bank can be seen from its profitability by measuring return on assets. The purpose of this research is to test the influence of Third Party Funds, Credit Risk, Loan To Deposit Ratio and Capital Structure on Profitability in Banking Companies Listed on the Indonesia Stock Exchange for the 2015-2019 period. The quantitative approach processes statistical data using multiple linear regression. This type of research is quantitative and causal in nature. The population in this study are 43 banking companies listed on the Indonesia Stock Exchange for the 2015-2019 period. The sample is 22 banks. The results of the research are Third Party Funds, Credit Risk, Loan To Deposit Ratio has no effect on Profitability in Banking Companies Listed on the Indonesia Stock Exchange Period 2015-2019. Capital Structure Influences Profitability in Banking Companies Listed on the Indonesia Stock Exchange for the 2015-2019 Period. Third Party Funds, Credit Risk, Loan To Deposit Ratio and Capital Structure Affect Profitability of Banking Companies Listed on the Indonesia Stock Exchange for the 2015-2019 Period.